Laparoscopic Approach in Colonic Diverticulitis: Dispelling Myths and Misperceptions. Issue 2 (April 2017) - Gralista, Panagiota; Moris, Demetrios; Vailas, Michail; Angelou, Anastasios; Petrou, Athanasios; Felekouras, Evangelos; Papalampros, Alexandros
Abstract : Background/Aim: Diverticular disease is a first-class health care problem and one of the most common gastrointestinal disorders in western industrialized countries, causing significant morbidity and mortality. In this review of the literature, we aim to assess the feasibility and effectiveness of the laparoscopic approach in both elective and emergency setting of diverticular disease. Materials and Methods: A bibliographic search of articles was performed using the electronic database Medline from PubMed. Of 341 articles identified, 279 were excluded, resulting in 62 full-text articles for review. Our final review included 16 articles. Results: The 16 articles included in the final review consisted of 6 retrospective studies, 5 prospective studies, 2 randomized controlled trials, 1 systematic review and meta-analysis, and 2 systematic reviews. Seven articles considered elective laparoscopic sigmoid resection, 7 articles evaluated laparoscopic peritoneal lavage, and 2 articles considered emergency laparoscopic sigmoid resection for perforated diverticulitis. The elective laparoscopic approach is feasible and safe. Laparoscopic peritoneal lavage has emerged as a safe and effective minimally invasive procedure for the treatment of perforated diverticulitis. Furthermore, in selected patients, emergency laparoscopic sigmoidectomy could also be feasible for perforated diverticulitis with generalized peritonitis. Conclusions: Laparoscopic approach can be a safe and effective option in both elective and emergency setting of diverticular disease. Large, prospective, randomized studies should be conducted to confirm these findings.